Dependence or Independence: Which Is the Dirty Word?. Issue 2 (11th May 2019) - Furlong, Mark
Abstract : We are suspicious of the mob, the gang, the enmeshed relationship. We also know no one can be an island. Our heroes tend to be loners – the solo detective, those who live free under the stars – but we esteem individuals who devote themselves to others. We want to belong, but we don't want to be owned. Like a game of Snakes and Ladders, there are trap‐doors and escalators in the theme Dependence or independence: Which is the dirty word? This paper explores the frisson and the conflicts in the complex relationships between dependence and independence. Following an introductory vignette, a schematic account is presented of the diverse ways 'dependence' and 'independence' can be theoretically interpreted including by systems theory. A deeper attention is then paid to honouring the importance of 'dependence' and 'independence' as key referents in everyday subjectivity. A first‐person account of mental illness is drawn on to illustrate this theme. A final section examines the implications for family therapy practice that arise from the above analysis.